FREQUENCY AND RISK FACTORS OF HEPATITIS B & C IN AFGHAN PATIENTS PRESENTING TO TERTIARY CARE HOSPITAL IN PESHAWAR: Hepatitis B & C in Afghan Patients - Khan, Zubair Ahmad; Shafiq, Mohammad; Shahab, Faseeh (Pakistan Armed Forces Medical Journal, 2015)
Objective: To document the frequency and risk factors of Hepatits B and C in Afghan patients presenting to a tertiary care hospital in Peshawar.Study Design:  Descriptive study.Place and Duration of Study: Rehman  Medical  Institute  (RMI),  Peshawar  from 1st January, 2012  to  31st December,  2012.                                                   Patients and Methods: A total of 2166 Afghan national were included in the study who underwent surgery in  RMI through consecutive, non-probability sampling. Hepatits B surface antigen (HBsAg) and anti-HCV antibody tests were performed by ELISA method. All  patients  who  were  positive  for  either  of  the  two  or  both  were  investigated  by  a  researcher-administered  questionnaire  to  find  the  risk  factors  for  seropositivity of hepatitis.Results: Out of a total of 2166 patients, 104 patients (4.8%) were found to be positive. Seventy-eight patients (75%) were HepBsAg positive while 24 patients (23%) were anti-HCV antibodies positive while 2 patients were positive for both viruses. Re-use of unsterilized syringes (23%) and history of previous surgery (19.2%) were the most common risk factors whereas no risk factor could be identified in 15 patients (14%). Seventy-nine patients (76%) were newly diagnosed at time of test while 25 patients (24%) were known cases of either HBV or HCV. Only one patient had clinical/laboratory features of chronic liver disease while no patient had underwent Hep B vaccination or had hepatocellular carcinoma.Conclusion: A high seroprevalance of HBV and HCV was found in this study. Reuse of unsterilized syringes, history of previous surgery and tattoos piercing were found to be the most common risk factors.